The Influence of Canva Media on Creative Thinking Skills in Science Learning Materials for Grade IV Students of UPTD SD Negeri 122399 - Malau, Elvionita; Simamora, Aprido; Siagian, Asister Fernando; Siagian, Gunaria (Jurnal Riset Ilmu Pendidikan, 2025)
The low creative thinking ability of students is caused by several factors including inadequate teaching materials and learning media that do not involve students because they use less varied learning models. This study aims to determine the Effect of Canva Media on Creative Thinking Ability in Science Learning Materials for Grade IV Students of UPTD SD Negeri 122399. The type of research used in this study is quantitative research. The research design used is experimental, with a pre-experimental design form that uses a "one group pretest posttest design" design, the sample in this study were 20 grade IV students of UPTD SD Negeri 122399. The instrument used in this study was a test. Based on the results of the research that has been carried out, there is an influence of Canva media on creative thinking skills in the science learning material of grade IV students of UPTD SD Negeri 122399. This is proven by the N-Gain Test showing that the average Pretest is 50.4 and the average Posttest is 85.8 where the lowest N-Gain Score is 0.39 and the highest N-Gain Score is 0.94, thus obtaining a gain of 0.78. This means that the class experienced an increase in critical thinking skills with a high category because (g) is more than or equal to 0.70. Based on these data, it is concluded that the application or use of Canva learning media has succeeded in increasing students' creative thinking skills compared to before.